THE IMPACT OF THE USE OF AN EMPLOYEE RECRUITMENT SYSTEM ON FILLING POSITIONS AT THE NIAS CLASS B SEARCH AND RESCUE OFFICE - Fiveten Rendyawan Hura; Meiman Hidayat Waruwu; Ayler Beniah Ndraha; Odaligoziduhu Halawa (LPPM YPITI, 2026)
This study aims to determine the effect of the use of an employee recruitment system on filling positions at the Nias Class B Search and Rescue Office. Problems arise because the recruitment process has not fully produced employees who meet the physical requirements, knowledge, and technical skills, thus impacting the effectiveness of filling positions. The research method used is quantitative with simple linear regression analysis using the SPSS version 26 program. The study population was employees of the Nias Class B Search and Rescue Office with 33 respondents. The results showed that the recruitment system had a positive and significant effect on filling positions. The t-test produced a t-value of 4.402 greater than t-table 1.696, with a significance value of 0.000 <0.05. The correlation coefficient value of 0.620 indicates a strong relationship between recruitment variables and filling positions. The coefficient of determination (R²) of 0.385 indicates that 38.5% of the variation in filling positions is influenced by the recruitment system, while the remaining 61.5% is influenced by other factors outside the study. In conclusion, the use of a selective, objective, and needs-based recruitment system plays an important role in ensuring the appropriate filling of positions in the Nias Class B Search and Rescue Office.